An integrated ASTER-based approach for mapping carbonatite and iron oxide-apatite deposits - Malainine, Cheikh-Elwali; Raji, Otmane; Ouabid, Muhammad; Khouakhi, Abdou; Bodinier, Jean-Louis; Laamrani, Ahmed; Youbi, Nasrrddine; Boumehdi, Moulay Ahmed (Taylor & Francis, 2021)
Mapping of carbonatites and related mineral deposits has occupied prominent place in mineral resource exploration programs given their potential to host valuable concentrations of critical metals such as rare earth elements and niobium. Based on spectral characteristics of most indicative minerals for these rocks, a mapping approach was developed using Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) data. The combination of band rationing outcomes with components from the principal component analysis and minimum noise fraction techniques highlighted the targeted rocks, with the excellent prospective zone representing ∼0.2% of the total investigated area. This approach was successfully applied to the Gleibat Lafhouda complex to rapidly delineate carbonatites and iron oxide-apatite ore outcrops. Results were validated through field observations and in-situ geochemical analysis using a portable X-ray fluorescence analyzer. Field data have also served as training data to perform a supervised classification, allowing further improvement of the mapping results.
Keywords: iron oxide-apatite ore; carbonatite; mineral resource exploration; ASTER data; remote sensing